Antibiotic resistance in Mexico: a brief overview of the current status and its causes - Carlos Amabile-Cuevas (Journal of Infection in Developing Countries)
As in many other developing countries, conditions that may foster antibiotic resistance in Mexico differ from developed countries, and so resistance prevalence. Fecal pollution and other traits of overcrowded, poor cities, might create ideal settings for selecting, exchanging and maintaining resistance traits. Medical abuse of antibiotics, along with low-quality drugs, are also present as in many developing countries. Self-prescription, a common yet unmeasured practice among Mexican population, may also contribute to increased resistance rates. Pneumococcal resistance towards penicillin and macrolides are the highest in Latin American countries, as is resistance of Salmonella and uropathogenic Escherichia coli towards ampicillin and sulfamethoxazole-trimethoprim; about one tenth of isolates of these gram-negative pathogens seem to produce extended-spectrum beta-lactamases (ESBL). High rates of multiple-drug resistant Mycobacterium tuberculosis are also found in Mexico, although there is no report of extensively drug-resistant strains. As to hospital-acquired pathogens, about a third of E. coli and Klebsiella isolates are ESBL-producers, and half of Staphylococcus aureus isolates are resistant to oxacillin (MRSA). Around 40% Pseudomonas aeruginosa isolates are resistant to ceftazidime, imipenem or levofloxacin. Although community-acquired MRSA, vancomycin-resistant enterococci, and other resistance problems found in developed countries, are not as common in Mexico, local issues are no small concern, and are disturbingly moving towards outpatients.